2023
DOI: 10.1002/pc.27257
|View full text |Cite
|
Sign up to set email alerts
|

Structural optimization to improve the dynamic performance of novel co‐curing damping sandwich composites

Abstract: Co‐cured damping composite structures have broad application prospects in high‐tech fields such as aerospace and space vehicles because of their low weight, large damping, and sufficient stiffness. In order to improve dynamic properties of conventional composite structures, a new type of damping composites embedded with multilayer viscoelastic film is proposed in this paper. Based on the complex modulus theory and vibration mechanics of composite plates and shells, vibration differential equation of composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…The results showed that as the number of alternate layers increased, the modulus of the material first increased and then decreased, and the composite loss factor also increased and then decreased; when the number of alternate layers is 7, the modulus of the material and the composite loss factor of the whole structure reach the peak at the same time. Zheng et al 14 used modal analysis and numerical simulation to study the influence of different damping layer thicknesses on the damping performance of the whole structure under free vibration. They found that the composite loss factor of the whole structure first increased and then decreased as the damping layer thickness increased.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that as the number of alternate layers increased, the modulus of the material first increased and then decreased, and the composite loss factor also increased and then decreased; when the number of alternate layers is 7, the modulus of the material and the composite loss factor of the whole structure reach the peak at the same time. Zheng et al 14 used modal analysis and numerical simulation to study the influence of different damping layer thicknesses on the damping performance of the whole structure under free vibration. They found that the composite loss factor of the whole structure first increased and then decreased as the damping layer thickness increased.…”
Section: Introductionmentioning
confidence: 99%